NATURAL RESOURCE EXPLOITATION AND STRUCTURAL TRANSFORMATION IN EAST KALIMANTAN: CHALLENGES FOR INCLUSIVE ECONOMIC DEVELOPMENT - Hakim, Abdul; Syarifuddin, Syarifuddin; Guntur, Yohanes Sri (Penelitian dan Pengembangan Ilmu, 2025)
East Kalimantan represents a critical case study of resource-dependent regional economies struggling to achieve structural transformation despite substantial natural resource endowments. This research examines the paradox of persistent extractive sector dominance and limited economic diversification in Indonesia's wealthiest province. Employing qualitative methodology through document analysis and secondary data synthesis, this study analyzes economic structure evolution during 2023-2025, revealing that mining and extractive industries continue to account for 68.4% of regional GDP while absorbing only 12.3% of the workforce. The research identifies three primary barriers to inclusive development: premature deindustrialization patterns, asymmetric capital accumulation favoring resource sectors, and institutional frameworks perpetuating enclave economy characteristics. Analysis of 2024 provincial data demonstrates that despite per capita income reaching IDR 187.4 million, poverty rates in extractive-dependent districts remain 3.2 percentage points above provincial averages. The findings challenge conventional resource curse narratives by demonstrating that institutional design rather than resource abundance itself constitutes the fundamental constraint. This research contributes to development economics literature by documenting how subnational resource governance structures mediate national-level development outcomes. Policy implications emphasize the necessity of redistributive mechanisms, forward linkage development, and deliberate industrial policy coordination to achieve structural transformation objectives aligned with Indonesia's 2045 vision.